The association of posttraumatic stress disorder, depression, and head injury with mid‐life cognitive function in civilian women. Issue 3 (30th December 2021) - Lawn, Rebecca B.; Jha, Shaili C.; Liu, Jiaxuan; Sampson, Laura; Murchland, Audrey R.; Sumner, Jennifer A.; Roberts, Andrea L.; Disner, Seth G.; Grodstein, Francine; Kang, Jae H.; Kubzansky, Laura D.; Chibnik, Lori B.; et al.
Abstract: Background: Despite evidence linking posttraumatic stress disorder (PTSD), depression, and head injury, separately, with worse cognitive performance, investigations of their combined effects on cognition are limited in civilian women. Methods: The Cogstate Brief Battery assessment was administered in 10, 681 women from the Nurses' Health Study II cohort, mean age 64.9 years ( SD  = 4.6). Psychological trauma, PTSD, depression, and head injury were assessed using online questionnaires. In this cross‐sectional analysis, we used linear regression models to estimate mean differences in cognition by PTSD/depression status and stratified by history of head injury. Results: History of head injury was prevalent (36%), and significantly more prevalent among women with PTSD and depression (57% of women with PTSD and depression, 21% of women with no psychological trauma or depression). Compared to having no psychological trauma or depression, having combined PTSD and depression was associated with worse performance on psychomotor speed/attention ( β  = −.15, p  = .001) and learning/working memory ( β  = −.15, p  < .001). The joint association of PTSD and depression on worse cognitive function was strongest among women with past head injury, particularly among those with multiple head injuries. Conclusions: Head injury, like PTSD and depression, was highly prevalent in this sample of civilian women. In combination, these factors were associated with poorer performance on cognitive tasks, a possible marker of future cognitive health. Head injury should be further explored in future studies of PTSD, depression and cognition in women.